Remote management of visits to points of interest in low-density rural territories - Cabral, Sérgio (2022)
Tourism is an important economic sector with particular importance for several countries and regions. For low-density rural territories, this sector can be an important driver of other sectors that guarantee jobs and local small and medium enterprises. However, in these regions mostly points of interest are dispersed and do not have a support structure to receive visitors and consequently most computer applications to support tourism are not suitable for these situations. This work describes a platform that uses technology to enhance the potential of opportunities to explore tourist attractions in low-density rural territories. This approach considers the particularities of these territories and the characteristics of existing points of interest. It provides mechanisms for tourism operators to make their points of interest available to be visited by tourists, without the need to spend a lot of resources and without the need of constant support from the tourism operators responsible for these points of interest. This approach may contribute to enhancing existing heritage in low-density rural territories, bringing new opportunities and unique experiences without requiring much human labor and enhancing the tourism benefit in low-density rural territories.